THE EFFECT OF PERSONAL AND SOCIAL FACTORS ON ONLINE BUYING INTEREST IN BINA MANDIRI GORONTALO UNIVERSITY STUDENTS - Sri Yuliana Halid; Titin Dunggio; Ely Ibrahim (LP2M Universitas Bina Mandiri Gorontalo, 2022)
This study aims to determine the effect of personal factors and social factors on online buying interest among Bina Mandiri University students, Gorontalo. This research uses descriptive quantitative method. Respondents of this study were students of the University of Bina Mandiri Gorontalo with a sample size of 90 people. Data analysis using multiple regression. The results showed that personal factors and social factors either partially or simultaneously had a positive and significant effect on online buying interest among students at Bina Mandiri University Gorontalo.